PENGARUH KOMPENSASI DAN WORK-FAMILY CONFLICT TERHADAP TURNOVER INTENTION DENGAN KOMITMEN ORGANISASI DAN STRES KERJA SEBAGAI VARIABEL MEDIASI - Hamdani, Hamdani; Muzahid, Mukhlisul (Ekonis: Jurnal Ekonomi dan Bisnis, 2023)
The purpose of this study was to analyze the effect of compensation and work-family conflict on organizational commitment, work stress and turnover intention, as well as the effect of organizational commitment and work stress on turnover intention. The next objective is to analyze the indirect effect of compensation and work-family conflict on turnover intention with organizational commitment and work stress as mediating variables. This research is a quantitative research conducted by survey method. Research data collection was carried out by distributing questionnaires to 93 research samples who were employees of the Politeknik Negeri Lhokseumawe. Sampling is determined by saturated sampling or census. However, of the 93 questionnaires distributed, only 81 questionnaires were returned and filled in completely, so that the final research sample was 81 respondents. Data analysis was performed using Structural Equation Modeling using SmartPLS and Sobel Test software. The results of the study show that compensation has no significant effect on organizational commitment and turnover intention; work-family conflict has a significant negative effect on organizational commitment, a significant positive effect on work stress and turnover intention; organizational commitment and work stress have no significant effect on turnover intention. Meanwhile, organizational commitment and work stress do not play a role in mediating the effect of compensation on turnover intention and work stress does not play a role in mediating the effect of work-family conflict on turnover intention.Keywords:  compensation, work-family conflict, organizational commitment, work stress and turnover intention